2006
DOI: 10.1002/dvdy.20892
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of tamoxifen‐regulated Cre activity in mice using a cartilage‐specific CreERT to assay temporal activity windows along the proximodistal limb skeleton

Abstract: Cartilage differentiation occurs over a broad time range from early embryonic development, when the mesenchymal condensations that give rise to cartilage models for future bone first appear, and continuing through adult life, when there is ongoing maintenance of articular joint surfaces and re-activation of cartilage formation after fracture. The chondrogenic response also figures in the pathogenesis of degenerative and inflammatory joint diseases. We have generated a transgenic line expressing tamoxifendepend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
280
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 243 publications
(292 citation statements)
references
References 33 publications
11
280
1
Order By: Relevance
“…It has been reported that transgenic Col2a1 promoters tend to be expressed not only in chondrocytes but also in early perichondrial progenitors (30). However, activation of the Col2a1-Cre ERT transgene used in this study in perichondrial cells does not occur unless the transgene is induced with tamoxifen before E13 when chondrogenic and perichondrial precursors are not yet segregated (25). Indeed, we have never observed lacZ + labeling in the perichondrium of R26R;Col2-Cre ERT mice (see Results).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It has been reported that transgenic Col2a1 promoters tend to be expressed not only in chondrocytes but also in early perichondrial progenitors (30). However, activation of the Col2a1-Cre ERT transgene used in this study in perichondrial cells does not occur unless the transgene is induced with tamoxifen before E13 when chondrogenic and perichondrial precursors are not yet segregated (25). Indeed, we have never observed lacZ + labeling in the perichondrium of R26R;Col2-Cre ERT mice (see Results).…”
Section: Discussionmentioning
confidence: 57%
“…The Col2-Cre ERT transgene used in this study has been reported to exhibit a low-level leakiness (25). Thus, we hypothesized that the phenotypes observed in Ext1-SKO mice are caused by leaky Cre activity.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is because Fgf10-positive cells are exclusively labeled upon tamoxifen injection, after which labeled cells can be traced and characterized. A previous report has shown that intraperitoneally administered tamoxifen reaches effective levels in the embryonic circulation within 12 hours, after which it is cleared from the pregnant female within 12 hours [18]. This 24-hour time frame allows accurate labeling of Fgf10-positive cells.…”
Section: Discussionmentioning
confidence: 90%
“…Cre recombinase fused to a mutated estrogen receptor protein was driven by the col2␣1 promoter were generated as reported earlier (21) and are described in Materials and Methods and shown schematically in Fig. 1A.…”
Section: Transgenic Mice In Whichmentioning
confidence: 99%